Education Effect Toward Enhance Adolescence Health Reproduction in Senior High School - Dwiesfiza Muharawita; Hardisman Hardisman; Firdawati Firdawati; Teguh Widodo (Postgraduate School, Universitas Negeri Padang, 2021)
The problem of Adolescent Reproductive Health (KESPRO) from time to time is increasing both qualitatively and quantitatively due to a lack of understanding of sexual and reproductive health. This study aims to determine the differences in the method of counseling and simulation games on the level of students' knowledge of reproductive health (KESPRO). The research method used a quasi-experimental design with a non-randomized control group pre-test-post-test which was conducted at State Senior High School 4 (SMAN 4) Padang City. The results showed that the extension method did not increase students' knowledge scores. Retention of students' knowledge after 3 days and 1 week of intervention with the extension method also did not increase students' knowledge scores. Based on the difference in the average score of students' knowledge about KESPRO after 1 week of intervention, the simulation game method group (1.04) was greater than the extension method (0.01) this means that the simulation game method can be better in maintaining memory students after 1 week of intervention about an information.